Efficacy of Ethanolic Plant Extracts of Zingiber officinale, Raphanus sativus, Rosa indica and Aloe vera against Heterotermes indicola - Ayesha Aihetasham; Qurat-ul-ain; Ramzan, Amera; Khan, Muhammad Xaaceph (BioScientific Review, 2021)
The current study was conducted to evaluate the anti-termitic potential of four common plant species, namely, Zingiber officinale, Raphanus sativus, Rosa indica, and Aloe vera. The worker and soldier cast of Heterotermes indicola were collected from Populus euramericana, old tree, University of the Punjab, Lahore, Pakistan. The extracts of plant species were prepared using Soxhlet Extractor. HR 2118 Philips grinder was used to crush the dried plant material into fine powder. Different concentrations were prepared and 0.5 ml of each concentration was poured on the filter paper and placed in the petri plate (arena). In laboratory bioassay, fifty active workers and five soldiers of H. indicola were added into each arena. The biological activity of ethanolic extracts of these plants was evaluated after 24 h and upto 96 h. The ethanol extract of Z. officinale caused the highest mortality (100%), while the lowest mortality (68%) was observed in R. indica extract. The LT50 for Z. officinale were 24.34, 40.40 and 64.7 h, for the concentrations of 10%, 5% and 3%, respectively. The findings suggested that these plant extracts can provide environmental friendly management of H. indicola. In A. vera, significant mortality was observed against H. indicola, that is, 94%, 64% and 44% on the exposure of 10%, 5% and 3% concentrations, respectively. While, LT50 were 34.66, 65.59, and 100.1 hours against 10%, 5% and 3% concentrations, respectively. In R. sativus, the mortality of H. indicola was 76%, 50% and 30%, while LT50 against them was 59.10, 86.20, and 127.3 h, against the concentrations of 10%, 5% and 3%, respectively. Lowest mortality was observed in R. indica, that is, 68%, 44% and 30%, while LT50 were 64.17, 94.58 and 125.5 h at the concentrations of 10%, 5% and 3%, respectively. This study reports that the extracts of Z. officinale, A. vera and R. Sativus have the potential to be used for termite control, especially against H. indicola, in order to minimize the damage caused by it. Keywords: Aloe vera, Heterotermes indicola, LT50, Raphanus sativus, Zingiber officinale Copyright(c) The Author